Home care of acute leukaemia patients: From active therapy to end‐of‐life and palliative care. The 3‐year experience of a single centre. (15th March 2019) - Capodanno, Isabella; Tamagnini, Enrica; Alfieri, Pierluigi; Codeluppi, Katia; Luminari, Stefano; Merli, Francesco
Abstract: Purpose: The aim of the study was to evaluate the feasibility and the potential effects of the Haematological Home Care (HHC) programme for acute leukaemia (AL) patients, either in active chemotherapy or in the terminal phase of disease. Methods: We retrospectively assessed a group of AL patients assisted at home in terms of number of hospitalisations, accesses to emergency department and place of death. We also used historical data to evaluate potential effects of HHC. Results: The study group consisted of 44 patients, 36 of whom (82%) required palliative treatment, and eight (18%) had ongoing active chemotherapy. The mean number of hospitalisations was 0.64 (range 0‐7) per patient, and the number of emergency department (ED) visits was 0.82 (range 0‐4) per patient. Place of death was at home for 51.4% of patients and in hospital for 40.5%. Considering a historical group of 17 patients assisted at home the rate of hospitalisations and ED visits were 2.53 (range 0‐9) and one (range 0‐3), respectively. Place of death was home and hospital in 6% and 65%, respectively. Conclusions: Haematological Home Care for AL patients is feasible and has potential positive effects in terms rate of hospitalisations and place of death.